Effects of an entertainment-education radio soap opera on family planning and HIV prevention in St. Lucia - Vaughan, Peter W. (2000)
Reports on the methods used and results of the broadcasting of an entertainment-education radio soap opera, Apwe Piezi in St. Lucia. Concludes that the broadcast influenced listeners to increase their awareness of contraceptives, improve important attitudes about fidelity and family relations and adopt family planning methods. Highlights important lessons for entertainment-education programmers.